Sedimentology of Some Turbidites and Related Rocks from the Cloridorme Group, Ordovician, Quebec - Beeden, David R. (My University, 1983)
Sandstones and shales of the γ4 Formation, Cloridorme Group (Middle Ordovician) are well-exposed on the northern coast of the Gaspé Peninsula, Quebec. The generally structureless, normally graded, medium to very coarse sandstones average 26 cm. in thickness and are interpreted as deposits of subcritical turbidity currents. Associated fine sandstones and siltstones were deposited from finer-grained turbidity currents which in some cases were the downcurrent equivalents of those which deposited coarse sandstones. Argillaceous sandstone layers containing clasts of siltstone and shale are the deposits of laminar debris flows.
Facies are organized into four unit types, the most important of which are sandstone packets and siltstone-shale interpacket units. Comparison of layer thickness trends in the actual section with those in a random section constructed from the same layer thickness population shows that the actual section is more ordered than expected under random processes. Layer thickness trends are superimposed on a smallerscale alternation of thick and thin layers.
Sandstone packets are interpreted as depositional lobes of a submarine fan. Packets are characterized by multiple or single thickening-upward sequences, with a thinning-upward sequence at their top representing gradual lobe abandonment. A channel-fill about 10 m. thick occurs in one packet. It does not show a thinning-upward trend.
Interpacket units also show dominantly thickening-upward sequences and are interpreted as lobe-fringe facies. Switching of submarine fan channels results in changes in lobe position so that vertical sections are characterized by alternation of lobe and lobe-fringe facies (outer fan facies association).
Comparison of other parts of the Cloridorme Group with the γ4 Formation allows their assignment to outer fan, fanfringe and basin plain facies associations. Submarine fans grew along the axis of the longitudinal basin rather than perpendicular to its margin. Opposite palaeocurrents in different parts of the group suggest that two oppositely-directed fans were present. Sedimentation rate during Cloridorme Group deposition was approximately 420 m./m.y.
Title: Sedimentology of Some Turbidites and Related Rocks from the Cloridorme Group, Ordovician, Quebec, Author: David R. Beeden, Location: Thode